Wildlife that affect plantations in Boyaca, and damage control on corn crops - Castillo-López, Israel Fernando; Rodríguez-Africano, Pablo Emilio; Montes-Pérez, Rubén Cornelio; González-Valderrama, Diana Milena (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The objective of this study was to identify the native fauna species that affect crops in the Valle de Tenza, and to test four non—letha| treatments to protect corn crops. The identification was carried out during five months of the year 2014. 150 suweys were applied to farmers from five municipalities in Valle de Tenza, following the ”snow ball" method; additionally, 10 Tomahawk traps, 30 Sherman traps, and five digital tracking cameras were used. The test for crop protection was carried out by applying four treatments based on some repellents, in the municipality La Capilla, from October 2014 to lanuary 2015, before and after harvesting the corn. A completely randomized treatment design was applied, and the damage was evaluated by analysis of variance and contrast of medians between treatments.The interviews indicated that 11 species affect the crops, specially Sciurus granatensis and Didelphis marsupiales. There are significant differences (P<0.01) between the total amount of damaged and healthy corn, regardless the type of treatment used. Nevenheless, no differences were found between treatments (P > 0.05).